Natural resources, structural change, and industrial development: Local content in Zambia - a faltering experience? - Wilfred C. Lombe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper traces the role of local content in Zambia's mining sector in supporting industrialization and economic diversification. It assesses productive linkages and manufacturing competitiveness during import-substitution industrialization and post-1991 liberalization and privatization, and the adequacy of the current policy environment. Despite diminished productivity and export competitiveness during import-substitution industrialization, that era was successful in terms of domestic manufacture of mining goods. Privatization and liberalization stymied local content capabilities, retarding industrialization and economic diversification. Post-2000 policies emphasize local content development and export competitiveness. Their success, however, depends on addressing continuing weaknesses in the regulatory environment; human and technological capital; endogenous entrepreneurship; and the macroeconomic environment.
Keywords: L5; L6; O2; O3; O4; 330; industrialization; local content; linkages; productivity; mining; manufacturing